Synthesis of ZnO Nanoparticles using Blue and IR Laser-Assisted Chemical Bath for Water Degradation - Hind Abdulgafour; Saifaldeen Abdalhadi; Rabah Shareef; Naser Ahmed (Nanochemistry Research, 2025)
Water pollution is a pressing global issue that demands constant evaluation of water resource policy. It is responsible for causing deaths and diseases worldwide, with an approximate daily death toll of 14000 people. This paper focuses on applying zinc oxide nanoparticles in photocatalytic degradation to treat dye-polluted (Methyl Orange solution) wastewater. Different synthesis methods, such as chemical bath deposition and laser-assisted chemical bath deposition, were employed to produce zinc oxide nanoparticles. The structural properties, crystallite size, morphology, particle size, optical properties, and degradation ability of the prepared ZnO nanoparticles were studied using Atomic Field Emission Scanning Electron Microscope (FESEM), X-Ray Diffraction (XRD), and UV-Vis Spectrophotometer. The synthesized ZnO nanoparticles were then used as catalysts in water degradation applications. The photocatalytic activity of the ZnO nanoparticles was evaluated, and the experiment conducted under UV light showed that pure ZnO synthesized by laser-assisted chemical bath deposition exhibited the highest rate of degradation, with 0.02521 min-1 and 71% photodegradation efficiency in 30 minutes.